2003
DOI: 10.1002/app.11828
|View full text |Cite
|
Sign up to set email alerts
|

Rheology of poly(n‐butyl methacrylate) and its composites with calcium carbonate

Abstract: Poly(n-butyl methacrylate) (PBMA) composites with calcium carbonate (CaCO 3 ) were prepared by in situ radical copolymerization of butyl methacrylate (BMA) and methacrylic acid (MA) with precipitated calcium carbonate. To compare the different rheological behaviors of the monomer mixtures with CaCO 3 and the composites, the steady and dynamic viscosities of BMA/MA/CaCO 3 and poly(BMA/MA/CaCO 3 ) were measured by means of steady and oscillatory shear flows. The viscosity of the mixture BMA/MA/CaCO 3 was found t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
13
0

Year Published

2005
2005
2017
2017

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 16 publications
(15 citation statements)
references
References 22 publications
1
13
0
Order By: Relevance
“…These findings are well in accordance with the literature: 17,24,25 With higher filler content, the melt viscosity of high-impact polystyrene/organomontmorillonite nanocomposites 24 and of P(BuMA) CaCO 3 composites 17 was recently found to be increased. The polymer viscosity itself was in addition found to be a function of the filler content.…”
Section: Resultssupporting
confidence: 92%
See 1 more Smart Citation
“…These findings are well in accordance with the literature: 17,24,25 With higher filler content, the melt viscosity of high-impact polystyrene/organomontmorillonite nanocomposites 24 and of P(BuMA) CaCO 3 composites 17 was recently found to be increased. The polymer viscosity itself was in addition found to be a function of the filler content.…”
Section: Resultssupporting
confidence: 92%
“…While nanosized silica, aluminum oxide, and CaCO 3 particles were already used as fillers for polymer compounding 11,17 or as scratch resistant coatings, 18,19 only few papers are published on fibers filled with inorganic particles. Commonly just low amounts of fillers (pigments) are applied for melt spinning.…”
Section: Introductionmentioning
confidence: 99%
“…P3 has a slightly higher glass transition temperature of T g ≈ −37 °C, which is in line with the same trend of the glass transition temperatures of the corresponding homopolymers PLMA (T g ≈ −65 °C) and P(PEGMA 300 ) (T g ≈ −61 °C). [23,38]…”
Section: Design and Characterization Of Crosslinkers And Linear Polymersmentioning
confidence: 99%
“…Liang and a coworker 28,29 in their studies on the MFR of ABS/CaCO 3 showed that ABS with 10% nano-CaCO 3 exhibited lower viscosity and a higher MFR than pure ABS with increasing wall shear stress. Chen et al 27 explained in research of PBMA/ CaCO 3 composites that the melting viscosity with 10% CaCO 3 was less than that of PBMA because of the lack of adhesion and probable voiding at the interface between CaCO 3 and the matrix.…”
Section: Rheological Properties Of the Ps Compositesmentioning
confidence: 99%
“…Chen et al 27 in their studies of poly(n-butyl methacrylate) (PBMA)/calcium carbonate composites, reported that the modulus of a composite with 10% CaCO 3 was less than that of PBMA, as observed from the melting viscosity, as a result of the lack of adhesion and probable voiding at the interface between CaCO 3 and the matrix. Liang and a coworker 28,29 revealed that acrylonitrile-butadiene-styrene (ABS) with 10% nano-CaCO 3 exhibited a lower viscosity and a higher melt flow rate (MFR) than pure ABS with increasing wall shear stress.…”
Section: Introductionmentioning
confidence: 99%